2022
DOI: 10.24018/ejbmr.2022.7.5.1612
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Production Capacity of Oil Country Tubular Goods Pipe Using Oee Methods

Abstract: The effectiveness of production equipment is very important to pay attention to maintain competition, coupling pipe threading process there has been an imbalance in the threading process time resulting in decreased output due to the number of rejected products which is decreasing in production capacity. To overcome the problem, the data was processed using mixed methods with a sequential explanatory approach, and the overall equipment effectiveness measurement method to analyze the calculation of availability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Therefore, FMEA can be used as the approach to increase OEE value. In addition, a study showed that Fishbone Diagram is used to identify problems that cause a company to be unable to achieve the ideal OEE (Solikhah & Nusraningrum, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, FMEA can be used as the approach to increase OEE value. In addition, a study showed that Fishbone Diagram is used to identify problems that cause a company to be unable to achieve the ideal OEE (Solikhah & Nusraningrum, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The machine effectiveness assessment is carried out using the OEE method to evaluate machine capability, minimize the impact of six big losses, and overcome the breakdown problem. In its implementation, OEE regards three measurement indicators: availability, performance efficiency, and quality rate (Solikhah & Nusraningrum, 2022). The results of the OEE will be the reference in determining the scope of improvement needed for the machine.…”
Section: Introductionmentioning
confidence: 99%